Ekstrakurikuler Sains sebagai Upaya Pengembangan Sikap Ilmiah dan Keterampilan Proses Sains Peserta Didik di SDIT Bina Anak Islam Krapyak - Muhammad Ikrom Karyodiputro (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
This study discusses the importance of science learning that is oriented towards giving direct experience to students. The aim of this research is to find out how the implementation of science extracurricular activities carried out at the Integrated Islamic Primary School of Bina Anak Islam Krapyak (SDIT BAIK), the development of scientific attitudes and scientific process skills of students through science extracurricular activities and scientific attitudes and process skills science shown by students who follow and who do not follow extracurricular science. This research is a qualitative research, which takes the setting in SDIT BAIK. Data collection is done by observation, interviews, documentation, and questionnaires. Analysis of research data through data reduction, data presentation, and data verification which is then checked for validity through data triangulation. The results showed that the implementation of extracurricular science activities at SDIT BAIK was held once a week which in its application used the role playing method that refers to the material in KUARK magazine and the experimental method based on material obtained from print and internet media in accordance with the level of knowledge of students. The development of scientific attitudes and science process skills for students is carried out through the application of learning that provides stimulants to the emergence of components of attitudes and skills related to scientific attitudes and science process skills. Every learning activity carried out in extracurricular science is oriented to the growth of the components of scientific attitudes and science process skills in students. Scientific attitudes and science process skills shown by students who take extracurricular activities are higher and deeper than students who do not participate in the activity.